Mulheres empreendedoras em Boa Vista-RR - Machado, Ana Carolina Lucena (2020)
In view of the great influence of gender in the context of Brazilian entrepreneurship, most women entrepreneurs experience discrimination, not to mention the great challenge of seeking a balance between their professional choices and personal demands (family). Encouraging entrepreneurship, the generation of jobs and income, providing dignity through occupation and reestablished urchasing power, re-signifying the importance of women's performance in the market and in society must be goals for the achievement of social and economic development and establishment of the democratic rule of law. Within the above, it is urgent to carry out studies on the subject, especially in a country with the continental dimensions of Brazil. Thus, this work deals with women entrepreneurs in Boa Vista - RR, aiming to carry out an explanatory and descriptive cross-sectional study of individual micro-entrepreneurs (MEIs) from Boa Vista - RR, using secondary data. Additionally, through the use of a specific questionnaire, the study also evaluated specific cases of 30 (thirty) women MEIs from Boa Vista - RR aiming to obtain the profile of the female population working in the city's labor market. Data collection through quantitative research aims to contribute to the analysis and verification of conflicting situations such as confusion between family and professional demands, in addition to work and personal demands. Finally, as it is a project idealized for a professional master's degree, in addition to the dissertation, the development of two additional products will be part of the study: a review article and a registered trademark at the National Institute of Industrial Property (INPI).